PENGARUH DANA PIHAK KETIGA (DPK), CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), RETURN ON ASSETS (ROA) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP VOLUME KREDIT YANG DISALURKAN BANK PERSERO (STUDI EMPIRIK PADA BANK PERSERO DI INDONESIA PERIODE 200 - Amastasiya, Fitriya Ayu; Saryadi, Saryadi; Wijayanto, Andi (Jurnal Ilmu Administrasi Bisnis, 2013)
ABSTRACTBank is an institution that serves as a financial intermediary. Banks accept deposits from the public money and then distribute it back in the form of loans. This research was conducted to examine the effect of Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return on Assets (ROA) and the Loan to Deposit Ratio (LDR) toward Credit Volume at The Government Banks (study Empyrical of Indonesia Government Banks in the period 2006-2011).The data used in this study is a secondary data obtained from Bank Indonesiaâ€™sÂ  libraries. The analysis technique using linear regression, while hypothesis testing using t - test and test - F at a significance level of 5%. The classical assumptions test used in this study include normality, multicollinearity, heteroscedasticity and autocorrelation test.Based on the research, it can be conclude that the third party funds and return on assets have a positive and significant impact on the volume of lending. Meanwhile, capital adequacy ratio, non performing loans and loan to deposit ratio are negative and not significant effect on the volume of lending. Simoultaneously there is a significant effect between third party funds, capital adequacy ratio, non performing loan, return on assets and loan to deposit ratio to the volume of loans.